If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 13y + 13 = 4y + 2 Reorder the terms: 13 + 13y = 4y + 2 Reorder the terms: 13 + 13y = 2 + 4y Solving 13 + 13y = 2 + 4y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-4y' to each side of the equation. 13 + 13y + -4y = 2 + 4y + -4y Combine like terms: 13y + -4y = 9y 13 + 9y = 2 + 4y + -4y Combine like terms: 4y + -4y = 0 13 + 9y = 2 + 0 13 + 9y = 2 Add '-13' to each side of the equation. 13 + -13 + 9y = 2 + -13 Combine like terms: 13 + -13 = 0 0 + 9y = 2 + -13 9y = 2 + -13 Combine like terms: 2 + -13 = -11 9y = -11 Divide each side by '9'. y = -1.222222222 Simplifying y = -1.222222222
| 13x+13=4y+2 | | 8f-93=27 | | x^2-4x+y^2+2y-5=0 | | -183=1+8(1-6n) | | 2y+1=4x+17 | | t^2-48t+576=0 | | 7x=1/2401 | | 11=-d+75 | | 15.07+x=27.05 | | 1.042=x-x^2 | | X^4+2x^3+8=0 | | -2-17=18+3x | | 2b^2-6b+4=0 | | 23=2y+5y | | 8(5-x)+4=7+4(x-6) | | 2.41+x=3.35 | | 8(5-x)+4= | | -8a+9a+-16a-(-17a)+-3a=20 | | 6.37+x=11.72 | | 25=16a-87 | | 6a+4whena=7 | | 12s-(2s+3)=65 | | 38=20+9g | | 6(6m-6)=-108 | | 4x^2-25=-4x+10 | | x-31+x+43+x=180 | | -8+9a+-16a-17a+-3a=20 | | 11/6=x/11 | | 4x^3-25=-4x+10 | | 4[e+4]=-12 | | 29.96+x=26.95 | | 7a^2+28a-35=0 |